News of the Annual Congress of the European Society of Cardiology in Munich: Research to Help Practical Medicine - S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
The article is devoted to the discussion of the main news  from the annual congress of the European Society of Cardiology (Munich, August 25-29, 2018). The results of just completed randomized clinical trials (RCTs) are reviewed. The RCTs presented at the congress were mainly devoted not to new drugs,  but to the features of the use of already known drugs,  which was important for clinical practice.